Experimental infection of calves by two genetically-distinct strains of rift valley fever virus - Wilson, William C.; Davis, A. Sally; Gaudreault, Natasha N.; Faburay, Bonto; Trujillo, J. D.; Shivanna, V.; Sunwoo, S. Y.; Balogh, A.; Endalew, A.; Ma, Wenjun; Drolet, B. S.; Ruder, M. G.; et al. (My University, 2016)
Recent outbreaks of Rift Valley fever in ruminant livestock, characterized by mass abortion and high mortality rates in neonates, have raised international interest in improving vaccine control strategies. Previously, we developed a reliable challenge model for sheep that improves the evaluation of existing and novel vaccines in sheep. This sheep model demonstrated differences in the pathogenesis of Rift Valley fever virus (RVFV) infection between two genetically-distinct wild-type strains of the virus, Saudi Arabia 2001 (SA01) and Kenya 2006 (Ken06). Here, we evaluated the pathogenicity of these two RVFV strains in mixed breed beef calves. There was a transient increase in rectal temperatures with both virus strains, but this clinical sign was less consistent than previously reported with sheep. Three of the five Ken06-infected animals had an early-onset viremia, one day post-infection (dpi), with viremia lasting at least three days. The same number of SA01-infected animals developed viremia at 2 dpi, but it only persisted through 3 dpi in one animal. The average virus titer for the SA01-infected calves was 1.6 logs less than for the Ken06-infected calves. Calves, inoculated with either strain, seroconverted by 5 dpi and showed time-dependent increases in their virus-neutralizing antibody titers. Consistent with the results obtained in the previous sheep study, elevated liver enzyme levels, more severe liver pathology and higher virus titers occurred with the Ken06 strain as compared to the SA01 strain. These results demonstrate the establishment of a virulent challenge model for vaccine evaluation in calves. © 2016 by the authors; licensee MDPI, Basel, Switzerland.
Citation: Wilson, W. C., Davis, A. S., Gaudreault, N. N., Faburay, B., Trujillo, J. D., Shivanna, V., . . . Richt, J. A. (2016). Experimental infection of calves by two genetically-distinct strains of rift valley fever virus. Viruses, 8(5). doi:10.3390/v8050145
Additional Authors: McVey, D. S.
Keywords: Cattle; Challenge Model; Pathogenicity; Rift Valley Fever; Rift Valley Fever Virus